Investigating the role of E-commerce marketing capabilities to achieve the strategic performance of tourism firms - Zhao, Jianchun; Zhang, Peilin (Frontiers in Psychology, 2023)
This study aims to explore the relationships between strategic performance, e-commerce marketing capabilities (ECMCs), the Internet of Things (IoT) and customer engagement. This study examines the direct association between ECMC and strategic performance. Current research also explores the customer engagement mediation between ECMC and strategic performance (SP). Furthermore, our study investigates the IoT moderation between ECMC and SP. We test our research hypotheses using data collected in the tourism sector in the context of digital commerce. The questionnaire is used to collect data through random sampling, and these data are useful as a basis for future research. By adding e-commerce capabilities, we show firms how to become more efficient and improve their strategic performance. Moreover, this study, by incorporating the findings of the existing literature, provides a strong foundation for studying the impact of ECMCs and customer engagement on strategic performance as well as the mediating role of e-trust. The results can be useful for managers who conduct digital business internationally, as they need to understand the importance of ECMCs. In fact, the adaptation of ECMCs to the organization enhances customer engagement and helps to improve strategic performance. The approach used in this study is in line with previous theoretical analyses and shows emerging patterns in international digital businesses. Moreover, this study adds insights to the e-commerce research by linking different dimensions to reach an in-depth understanding of each item that is affected by ECMCs.